2013
DOI: 10.1371/journal.pone.0066067
|View full text |Cite
|
Sign up to set email alerts
|

Functional Integration of the Conserved Domains of Shoc2 Scaffold

Abstract: Shoc2 is a positive regulator of signaling to extracellular signal-regulated protein kinases 1 and 2 (ERK1/2). Shoc2 is also proposed to interact with RAS and Raf-1 in order to accelerate ERK1/2 activity. To understand the mechanisms by which Shoc2 regulates ERK1/2 activation by the epidermal growth factor receptor (EGFR), we dissected the role of Shoc2 structural domains in binding to its signaling partners and its role in regulating ERK1/2 activity. Shoc2 is comprised of two main domains: the 21 leucine rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 59 publications
(68 reference statements)
1
49
0
Order By: Relevance
“…Our earlier studies suggested that, in addition to tethering and enforcing physical proximity between Ras and RAF-1, the Shoc2 function extends to the coordination and integration of positive and negative ERK1/2 feedback loops (41). Thus, we set out to identify the proteins of the Shoc2 feedback loops and the mechanism that regulates Shoc2 function.…”
Section: Resultsmentioning
confidence: 99%
“…Our earlier studies suggested that, in addition to tethering and enforcing physical proximity between Ras and RAF-1, the Shoc2 function extends to the coordination and integration of positive and negative ERK1/2 feedback loops (41). Thus, we set out to identify the proteins of the Shoc2 feedback loops and the mechanism that regulates Shoc2 function.…”
Section: Resultsmentioning
confidence: 99%
“…S3A) (Jeoung et al, 2013). We found that a fragment of Shoc2 corresponding to leucine-rich repeats (LRRs) 20 to 21 (ΔN-19) was sufficient for PSMC5 binding (Fig.…”
Section: Psmc5 Binds To Leucine-rich Repeat 21 Of Shoc2mentioning
confidence: 90%
“…Shoc2 interacts with its signaling partners, Ras and RAF-1 through the unstructured N-terminal domain and the leucine-rich curvature of Shoc2 is left available to interact with additional components of the scaffolding module Jeoung et al, 2013). To further investigate the composition and dynamics of the Shoc2 scaffold complex, we performed a yeast two-hybrid screen in the human adult and fetal heart library using full-length Shoc2 as a bait as described previously .…”
Section: Interaction Of Shoc2 With Psmc5mentioning
confidence: 99%
See 2 more Smart Citations